Industry‐Specific Capital and the Wage Profile: Evidence from the National Longitudinal Survey of Youth and the Panel Study of Income Dynamics - Parent, Daniel (Journal of Labor Economics, 2000)
Using data from the National Longitudinal Survey of Youth (1979-96) and the Panel Study of Income Dynamics (1981-91), I seek to determine whether there is any net positive return to tenure with the current employer once we control for industry-specific capital. Including total experience in the industry as an additional explanatory variable, I show that the return to seniority is markedly reduced using GLS while it virtually disappears using IV-GLS, at both the one-digit and three-digit levels. Therefore, it seems that what matters most for the wage profile in terms of human capital is industry-specificity, not firm-specificity. Copyright 2000 by University of Chicago Press.